2022
DOI: 10.3390/f13020178
|View full text |Cite
|
Sign up to set email alerts
|

The Box Tree Moth: An Invasive Species Severely Threatening Buxus Natural Formation in NW Italy

Abstract: (1) The box tree moth (BTM), Cydalima perspectalis Walker, represents one of the recent examples of exotic insect pests native to Asia accidentally introduced in Europe by the nursery trade. In Europe, BTM develops on Buxus sempervirens L., causing significant damage to ornamental and natural plants. (2) Basic aspects of BTM biology were investigated at three sites in the NW Alps, where B. sempervirens occurs on rocky slopes, forming a protected habitat. In 2019–2021, we evaluated: (i) the seasonal flight acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Since then, the non-native moth has spread across Europe, causing devastating damage to ornamental box trees (Buxus spp.) in private gardens, cemeteries, and urban and historical parks [3,4] and also affecting natural boxwood stands (Buxus sempervirens L.) in southern and western Europe [5][6][7][8]. More recently, C. perspectalis has been recorded in North America (first reported in Toronto, Canada, in 2018 [9]) and in Africa (first detected in Constantine, Algeria, in 2018 [10]).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the non-native moth has spread across Europe, causing devastating damage to ornamental box trees (Buxus spp.) in private gardens, cemeteries, and urban and historical parks [3,4] and also affecting natural boxwood stands (Buxus sempervirens L.) in southern and western Europe [5][6][7][8]. More recently, C. perspectalis has been recorded in North America (first reported in Toronto, Canada, in 2018 [9]) and in Africa (first detected in Constantine, Algeria, in 2018 [10]).…”
Section: Introductionmentioning
confidence: 99%
“…The fast invasion of Europe by the box tree moth: an additional example coupling multiple… has been recorded only on Buxus species (Wan et al 2014;Matošević et al 2017;Ferracini et al 2022). In its native range, the insect has been reported to develop on several Buxus species, and three other host plants (Ilex purpurea, Euonymus alatus and E. japonicus) (Wan et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the use of these three plants as host by BTM has recently been debated. Several performance experiments done with invasive populations showed that BTM larvae were only able to develop on Buxus species, suggesting that the moth is an herbivorous specialist of this plant genus (Brua 2014;Matošević et al 2017;Ferracini et al 2022). In Asia, approximately 40 native species of Buxus occur, among which at least 15 species are found in China (Kohler and Brückner 1989;Fang et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fewer works have also been carried out to detect possible native biotic factors of mortality (predators, parasitoids, entomopathogenic microorganisms and nematodes) capable of attacking or infecting the pest in Europe; Oltean et al [16] summarized data from the literature. The Diptera Compsilura concinnata (Meigen, 1824) was found to parasitize C. perspectalis larvae at a low rate in France [18]; Ferracini et al [19] found another tachinid, Pseudoperichaeta nigrolineata (Walker, 1853), in Italy; and a sirphid species, Xanthandrus comtus (Harris, 1780), was found by Las Heras et al [20] predating the larvae in Catalonia. Bird et al [21] reported, for the first time in Britain, the parasitism of the boxwood moth by P. nigrolineata and by a pteromalid, Stenomalina cf.…”
Section: Introductionmentioning
confidence: 99%